2022
DOI: 10.2196/33038
|View full text |Cite
|
Sign up to set email alerts
|

Lessons for Uptake and Engagement of a Smartphone App (SURE Recovery) for People in Recovery From Alcohol and Other Drug Problems: Interview Study of App Users

Abstract: Background Mobile health apps promoting health and well-being have substantial potential but low uptake and engagement. Barriers common to addiction treatment app uptake and engagement include poor access to mobile technology, Wi-Fi, or mobile data, plus low motivation among non–treatment-seeking users to cut down or quit. Working with people who used substances, we had previously designed and published an app to support recovery from alcohol and other drug problems. The app, which is available for… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…The research articles for the final review numbered 18 [53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69][70]. The PRISMA flowchart for literature search is presented in Figure 1.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The research articles for the final review numbered 18 [53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69][70]. The PRISMA flowchart for literature search is presented in Figure 1.…”
Section: Methodsmentioning
confidence: 99%
“…In many of the articles the background data collected included the age, gender, educational background and/or employment status of those using the application [56,58,[61][62][63][64]68]. Rather than on changes in substance abuse, our research interest centred more on non-demographic factors predisposing to the use of the application even though research has shown that both gender [68] and age [53,70] frequently need to be considered regarding…”
Section: Background Situation Information and Skillsmentioning
confidence: 99%
See 3 more Smart Citations